Covert Derogations and Judicial Deference: Redefining Liberty and Due Process Rights in Counterterrorism Law and Beyond - Fenwick, Helen; Phillipson, Gavin (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2011)
This article considers the use of control orders in the United Kingdom as an example of one of the most important legal aspects of the “war on terror”: the development, alongside the criminal justice approach, of a pre-emptive system. It argues that in relation to such orders the executive has in effect sought to redefine key human rights in a manner that, at its most extreme, amounts to covert derogation, and that both Parliament and the judiciary have been to an extent drawn into and made complicit in this process. It highlights key aspects of this story in order to illustrate some broader points about the role of judges, Parliament, and the rule of law in response to such exceptional measures. It argues that the attempted minimization of the ambit of rights, the spreading use of secret evidence, and the damaging constitutional impact of excessive judicial deference, are of great significance beyond UK counterterrorism law and can help illuminate both the opportunities and the dangers in constitutional dialogue.